Senyapan dalam Ujaran pada Video (Eksekutif) Jokowi Soal IKN, Gibran, dan “Adili Jokowi” dalam Channel YouTube Najwa Sihab: Kajian Psikolinguistik - Ningtyas, Afrilia; Ira Gustina Sari; Fatmawati Fatmawati (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Pauses are a linguistic phenomenon that frequently appear in speech production, particularly in formal and semi-formal communication contexts that require a high level of linguistic caution. This study employs a psycholinguistic approach that examines the relationship between mental processes and language in spoken discourse. The purpose of this study is to describe the forms of pauses and the factors causing pauses in the utterances of President Joko Widodo in the Eksekutif Najwa Shihab video, which discusses issues related to the National Capital City (IKN), Gibran Rakabuming Raka, and the public demand “Adili Jokowi.” This research uses a descriptive qualitative method. The research data consist of utterances containing pauses obtained from Najwa Shihab’s YouTube videos. Data were collected using listening and note-taking techniques, while data analysis employed the extralingual equivalent method. The results of the study indicate the presence of two types of pauses, namely silent pauses and filled pauses. Filled pauses include pauses in the form of sounds and words. The factors causing pauses include the speaker’s caution in choosing words, unpreparedness in delivering ideas comprehensively, and the speaker’s effort to maintain the intended meaning of utterances in order to avoid misinterpretation.